PENELITIAN TINDAKAN KELAS DALAM KONTEKS PEMBELAJARAN BAHASA JERMAN - Rikfanto, Aditya; Rachmadi, Sridanto Farras (Diksi, 2021)
(Title: Class Action Research in the Context of German Language Learning). As a means of problem-solving, research methods continue to evolve. In the ’40s began to be known action research, and this research was also applied in the classroom or called Class Action Research (CAR). This type of research is becoming increasingly popular to evaluate the learning process of German Language Teaching. However, the focus of CAR talks in German language learning is still likely to be rare. This paper discusses the characteristics and application of CAR in German language learning. In addition, this article also reviews the situation of German learning in general. Thus the article can contribute scientifically to teachers and educators in improving performance in their fields. Keywords: Action Research, CAR, Learning, German Language